HABSBURG STRATEGY IN EDUCATION: EMPIRE-WIDE TRENDS AND WEST UKRAINIAN REALITIES - Монолатій, І. С. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article analyzes the strategy of governmet of the Austro-Hungaria in secondary and higher education in Galicia and Bukovina late XIX – early XX centuries. Substantiated the thesis that there is, as a tool of ethnic assimilation of «foreign», the government used, and education. This is evidenced by the fact of discrimination in the allocation of resources, ethnicity, disability ethnic minorities to secondary and higher education. The latter is not only difficult to achieve their highest qualification and high social status, but also loses the opportunity to implement the values ​​of welfare. The author analyzes the facts of restrictions by local authorities in the field of secondary and higher education. The correlation nationalities and speaking students of classical and technical colleges of Cisleithania and Lviv and Chernivtsi Universities and the Lviv Polytechnic. Stated that it is a fact of gradual reduction in the number of students-Ukrainian, while ignoring them purely urban, practical disciplines. Examples of latent value conflicts identified and student fights and riots - an example of the group, which owns a number of properties of status, are ranked differently in different status hierarchies, feels frustrated and prone to unrest.